The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0100-736x2011001100008
|View full text |Cite
|
Sign up to set email alerts
|

Testes de ELISA e vírus-neutralização na detecção de anticorpos contra o vírus da diarréia viral bovina no leite

Abstract: Pesq. The success of control/eradication programs of bovine viral diarrhea virus (BVDV) infection necessarily includes the identiϐication and elimination of persistently infected (PI) animals. Since these animals continuously shed virus in secretions and excretions, the prevalence of antibodies in herds with PI animals is often high, and with high titers. Because of these characteristics, bulk milk samples were subjected to two serological techniques in order to establish the most appropriate in conducting sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
2
0
1
Order By: Relevance
“…Furthermore, 101 of the 400 samples (25.25%) had an antibody titer ≥80 on VN (Table 4). This can be because of the presence of animals in the acute phase of the disease and/or persistently infected animals (PIs), (STURZA et al, 2011) since herds that have PIs can be identified using serology, as the presence of the virus results in high levels of antibodies in most animals (HOUE, 1999). It is also worth noting that iELISA presented a positive result for all samples with an antibody titer ≥80 on VN.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 101 of the 400 samples (25.25%) had an antibody titer ≥80 on VN (Table 4). This can be because of the presence of animals in the acute phase of the disease and/or persistently infected animals (PIs), (STURZA et al, 2011) since herds that have PIs can be identified using serology, as the presence of the virus results in high levels of antibodies in most animals (HOUE, 1999). It is also worth noting that iELISA presented a positive result for all samples with an antibody titer ≥80 on VN.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have estimated dairy and beef herd prevalence around the world (Paton et al., ; Ståhl et al., ; Thobokwe et al., ; Brülisauer et al., ), and it is well known that BVDV is also spread within Brazilian herds (Canal et al., ; Chaves et al., ). However, most studies previously conducted in Brazil used non‐probabilistic samples, and many have introduced bias into the prevalence and odds estimation (Dias and Samara, ; Flores et al., ; Chaves et al., ; Sturza et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Ensaio imunoenzimático de adsorção -ELISAO ELISA é O teste de ELISA direto (ELISA BVDV-Ag) pode se basear no método de captura e pode ser utilizado em diferentes matrizes, como plasma, sangue total, biópsia de orelha e de leite(OMSA, 2018).NoBrasil, Felicio et al (2016), no período de Julho de 2015 a Julho de 2016, detectaram 0,02% (186/11.010) de bovinos positivos para BVDV pelo teste de ELISA BVDV Ag/Serum Plus (Idexx Laboratories HerdChek ® ). Esses animais eram provenientes de 12 Estados Brasileiros: São Paulo, Minas Gerais, Roraima, Rio Grande do Sul, Mato Grosso, Mato Grosso do Sul, Bahia, Distrito Federal, Goiás, Rio de Janeiro, Paraná e Santa Catarina, das quais 118 pertenciam ao Estado de São Paulo, 13 de Roraima, 54 de Mato Grosso e um do Distrito Federal indicando a presença desse importante patógeno nos rebanhos Brasileiros e da necessidade de mais estudos quanto a genotipagem com a finalidade de ações profiláticas efetivas Sturza et al (2011). compararam os testes de ELISA indireto e neutralização viral na detecção de anticorpos em tanque de leite e em amostras de leite individual com a finalidade de detecção de níveis de anticorpos e, posteriormente orientar a busca de animais PI na propriedade, pois esses animais são responsáveis em disseminar o vírus entre os animais susceptíveis.…”
unclassified